MEDIASI PROFITABILITAS PADA HUBUNGAN ANTARA GOOD CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Taufik Taufik (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. This research aimed to analyze the mediating effect of profitability on therelationship of good corporate governance and firm size to corporate socialresponsibility. The population were 29 firm of Indonesia trusted companies based onthe survey of Indonesia Institute for Corporate Governance in Indonesia StockExchange from 2014 – 2015. The sampling technique used was purposive sampling.Based on the sampling criteria, the number of selected samples were 20 firms. Dataanalysis used was path analysis method. The research findings were: 1). Goodcorporate governance had no effect to profitability and corporate social responsibility,2). Firm size and profitability had positive influence on corporate socialresponsibility.3). Firm size had negative effect to profitability. 4). Profitability did notmediate the relationship of good corporate governance and firm size to corporate socialresponsibility.